Effect of copper addition on the microstructure, mechanical, thermal, and magnetic properties of Fe-Ni-Cu alloys - Delice, Serdar; Gungunes, Hakan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In this study, FeNiCu alloys with two different copper contents were produced by arc melting. The aim was to investigate the effects of Cu content on the microstructural, mechanical, thermal, and Mössbauer properties of the alloys. Microstructures were examined using SEM micrographs. Vickers hardness tests were conducted to evaluate mechanical strength. Thermal behavior was analyzed using DSC. Magnetic characteristics were studied by Mössbauer spectroscopy. SEM analysis showed the presence of martensitic structures in both alloys, with the alloy containing more Cu exhibiting a higher amount of martensite. Hardness increased from 169.1 HV to 190.2 HV as Cu content increased. DSC results confirmed the martensitic transformation. The alloy with higher Cu content showed a higher transformation temperature and greater transformation energy released. Mössbauer spectra indicated the presence of both magnetically ordered and non-ordered phases in both alloys. Hyperfine parameters demonstrated changes in the local atomic environment due to Cu addition. The weak singlet obtained was associated with the FCC phase. The two sextets were attributed to ferromagnetic BCC phases arising from different environments of the Fe atom. The other sextet, with a low internal magnetic field of around 18 T, was ascribed to possible Ni- and/or Cu-rich surroundings of the Fe atom. Overall, increasing Cu in the alloy altered the microstructure, improved hardness, shifted the martensitic transformation temperature, and modified the magnetic hyperfine interactions. These results may aid in designing advanced Fe-based materials for structural and magnetic applications.